2009
DOI: 10.1021/jm9007856
|View full text |Cite
|
Sign up to set email alerts
|

The Application of Phosphoramidate Protide Technology to Acyclovir Confers Anti-HIV Inhibition

Abstract: Recently it has been reported that phosphorylated acyclovir (ACVa) inhibits human immunodeficiency virus type 1 (HIV-1) reverse transcriptase in a cell free system. To deliver phosphorylated ACV inside cells we designed ACV monophosphorylated derivatives using ProTide technology. We found that the L-alanine derivatived ProTides show anti-HIV activity at noncytotoxic concentrations; ester and aryl variation was tolerated. ACV ProTides with other amino acids, other than L-phenylalanine, showed no detectable acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
84
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 72 publications
(89 citation statements)
references
References 16 publications
5
84
0
Order By: Relevance
“…The stereo-selective hydrolysis of an acyclovir phosphoramidate prodrug was previously demonstrated by using carboxypeptidase Y, a structural homolog of cathepsin A (31,32). A computer model of carboxypeptidase Y docked with a phosphoramidate prodrug in the active site suggested that positioning of the carbonyl moiety of the carboxyl ester with the R-phosphate diastereoisomer was more preferable for catalysis than with the S-diastereoisomer (31). However, they failed to identify which diastereoisomer was preferentially hydrolyzed by carboxypeptidase Y in their biochemical assay.…”
Section: Discussionmentioning
confidence: 99%
“…The stereo-selective hydrolysis of an acyclovir phosphoramidate prodrug was previously demonstrated by using carboxypeptidase Y, a structural homolog of cathepsin A (31,32). A computer model of carboxypeptidase Y docked with a phosphoramidate prodrug in the active site suggested that positioning of the carbonyl moiety of the carboxyl ester with the R-phosphate diastereoisomer was more preferable for catalysis than with the S-diastereoisomer (31). However, they failed to identify which diastereoisomer was preferentially hydrolyzed by carboxypeptidase Y in their biochemical assay.…”
Section: Discussionmentioning
confidence: 99%
“…These compounds showed anti-HIV activity in the absence of HHV infection, demonstrating their nucleoside kinase independence. 4, 5 These findings were also supported in a different study, where ACV phosphate prodrugs showed a full retention of antiviral activity against HSV-1 and VZV thymidine kinase (TK)-deficient strains. 6 Unfortunately, these compounds proved to be somewhat cytotoxic in some assays.…”
Section: Introductionmentioning
confidence: 58%
“…The final coupling of the nucleoside 25 has been performed using an excess of the phosphorochloridate (33) (3 eq) in the presence of t BuMgCl (3eq) following the procedure reported by Uchiyama [17] and extensively used for the synthesis of the ProTides [18]. The desired compound 34 was obtained as a mixture of two diastereoisomers confirmed by the presence of two peaks in the 31 P NMR (2.92, 2.27).…”
Section: Chemical Synthesismentioning
confidence: 99%